The Relationship Between Reef Fish Biodiversity and Coral Reef Health in Jepara Regency, Central Java, Indonesia - Suryono, Suryono; Diah Permata, Wijayanti; Samsudin PJ, Nur Taufiq; Ibnu, Pratikto; Handung, Nuryadi (Universitas Negeri Semarang, 2025)
Coral reefs are vital habitats for numerous fish species, providing food, shelter, and breeding grounds. In Jepara Regency, Central Java, Indonesia, these ecosystems are threatened by human activities and natural disturbances. This study aimed to assess the biodiversity of reef fish in relation to coral health degradation. Researchers used the Line Intercept Transect (LIT) and Underwater Visual Census (UVC) methods to evaluate fish abundance and coral coverage across three locations with six sampling stations. 936 reef fish individuals, representing 35 species and 14 families, were recorded, with the Pomacentridae family being the most prevalent. The highest coral coverage, categorized as fair, was found at Location II (Blebak Beach) at Stations 3 and 4, with coverage of 27.93% and 25.61%, respectively. This coral coverage was positively correlated with reef fish abundance, with counts of 238 and 246 individuals (average ± SD: 242 ± 5.65). The biodiversity index indicated a dominance index (D) ranging from 0.05 to 0.14 (in the fair category), a high evenness index (E) between 0.75 and 1, and a low dominance index (D) between 0.05 and 0.14. A significant correlation was found between coral coverage and reef fish numbers (P < 0.05, R² = 0.8702), with a linear regression equation of y=6.26+67.71. The findings suggest that the health of coral reef ecosystems significantly affects reef fish populations. Hereafter, the healthiness of this ecosystem will support the scientific core development of Marine Sciences as well as fulfill society's needs (economically).